Vitamin B12 deficiency in patients of type 2 diabetes mellitus treated with metformin: a cross section observational study from a tertiary care centre in Sub-Himalayan region of North India - Nand, Laxmi; Mahto, Sunita; Garg, Dalip K.; Kumar, Bhupender (International Journal of Research in Medical Sciences, 2020)
Background: Metformin is first line of treatment in type 2 diabetes mellitus (T2DM). It has been reported to be associated with vitamin B12 deficiency with variable results in various studies. The aim of our study is to correlate metformin use and vitamin B12 levels in patients of T2DM with high prevalence in Sub-Himalyan region of north India. Methods: The study was conducted from August 2017 to July 2018 enrolling 124 patients, aged 18 years and above with T2DM taking metformin treatment for >4 months. Vitamin B12 levels were estimated and the levels <200, 200-300 and >300 pg/ml were defined as having definite deficiency, borderline deficiency and normal levels respectively. Results: A total of 124 patients included 66 (53.2%) male and 58 (46.8%) female patients with T2DM on metformin treatment. The mean vitamin B12 level was found significantly low, 176.23±60.96 pg/ml and 18 (14.5%) patients were found to have significant vitamin B12 deficiency and 8(6.5%) patients, borderline deficiency in longer duration of metformin use for >10 years (p<0.001). Vitamin B12 deficiency was found significantly more in 14 (11.3%) patients taking lower doses ≤1000 mg/day of metformin compared to higher doses, a negative correlation. Peripheral neuropathy was significantly present in 15.3% of patients in metformin induced vitamin B12deficiency. Conclusions: Vitamin B12 deficiency was found to be significantly correlated to longer duration of metformin treatment and neuropathy in T2DM but negatively correlated to higher doses of metformin. Therefore, we recommend the assessment and supplementation of vitamin B12 in metformin use in T2DM, compromising financial burden but not the outcome of its deficiency.